Molecular pharmacology of the cannabinoid receptor type-1 in primary skeletal muscle - Mohd Noor, Mohd Fadly; Bennett, Andrew J.; Tsintzas, Kostas (2015)
Endocannabinoid system plays an important role in the regulation of energy balance and metabolism. This study aimed to determine the molecular pharmacological properties of the cannabinoid receptor type-1 (CB1) in term of agonism and antagonism upon gene expression in rat primary skeletal muscle myotube. The myotube were treated for 24 hours with 10nM Arachidonoyl 2'-Chloroethylamide (ACEA) or 100 nM Rimonabant (RIM) in normal and lipid-free serum media. Gene expression of lipocalin 2, neuropeptide Y, pseudokinase tribbles homolog-3 and nuclear receptor subfamily 4 group A member 1, 2 and 3 were determined via Taqman qRT-PCR. Previous microarray analysis showed all of the genes above were regulated by CB1 inhibition. Current results revealed ACEA and RIM had no effect upon expression of the genes described above; rather they were upregulated in the lipid-free medium. Reintroduction of free fatty acids (FFA)- palmitic, linoleic and oleic acids into the lipid-free serum media reverted the gene expression back to level observed in normal serum media; which suggest that gene expression is regulated by the levels of FFA in the serum and not by endocannabinoids. Additionally, we have developed a contractile myotube model using electrical pulse stimulation (EPS). Assays of the culture media showed significant increase in lactic acid and reduction in glucose concentration together with an increase in GLUT4 gene expression in EPS stimulated myotube as compared to non-stimulated cells.